Q-switched 2 μm thulium bismuth co-doped fiber laser with multi-walled carbon nanotubes saturable absorber - Norazlina, Saidin; Zen, D.I.M.; Ahmad, Fauzan; Haris, Hazlihan; Ahmad, H; Dimyati, Kaharudin; Harun, Sulaiman Wadi; Halder, Arindam; Paul, Mukul Chandra; Pal, Mrinmay C.; Bhadra, Shyamal Kumar (Elsevier Ltd, 2016)
We report a passively Q-switched fiber laser operating at 1900 nm region using the newly developed Thulium Bismuth co-doped lithium-alumino-germano-silicate fiber (TBF) as a gain medium in conjunction with a multiwall carbon nanotubes (MWCNTs) based saturable absorber (SA). The TBF and MWCNTs are fabricated and prepared in-house. By increasing the 802 nm pump power from 106.6 to 160 mW, stable generation of Q-switched TBFL has been obtained at 1857.8 nm wavelength. The pulse repetition rate varies from 12.84 to 29.48 kHz while pulse width is increased from 9.6 to 6.1 µs. The performance of the laser is also compared with the Q-switched TDFL, which was obtained using a similar MWCNTs SA and pump wavelength. The Q-switched TDFL generates an optical pulse train with a repetition rate increasing from 3.8 to 4.6 kHz and pulse width reducing from 22.1 to 18.3 μs when the pump power is tuned from 187.3 to 194.2 mW. This shows that the TBFL performs better than the TDFL in terms of threshold pump power, repetition rate and pulse width.